1999
DOI: 10.1037/0278-7393.25.5.1177
|View full text |Cite
|
Sign up to set email alerts
|

What is the connection between true and false memories? The differential roles of interitem associations in recall and recognition.

Abstract: Veridical memory for presented list words and false memory for nonpresented but related items were tested using the Deese/Roediger and McDermott paradigm. The strength and density of preexisting connections among the list words, and from the list words to the critical items, were manipulated. The likelihood of producing false memories in free recall varied with the strength of connections from the list words to the critical items but was inversely related to the density of the interconnections among the list w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
141
1
8

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(168 citation statements)
references
References 27 publications
18
141
1
8
Order By: Relevance
“…As the results of regression analyses have shown (Roediger, Watson, McDermott, & Gallo, 2001), this variation in false-recall level is largely due to differences in the associative strength between the lists' critical item and the noncritical ones. In fact, the degree to which the noncritical items evoke associations to the critical item nicely predicts false recall (see also McEvoy, Nelson, & Komatsu, 1999). Following these results, high false-recall levels indicate a higher degree of interconnections between the noncritical items and the critical one, and low false-recall levels indicate a lower degree.…”
Section: Drm Item Listsmentioning
confidence: 54%
“…As the results of regression analyses have shown (Roediger, Watson, McDermott, & Gallo, 2001), this variation in false-recall level is largely due to differences in the associative strength between the lists' critical item and the noncritical ones. In fact, the degree to which the noncritical items evoke associations to the critical item nicely predicts false recall (see also McEvoy, Nelson, & Komatsu, 1999). Following these results, high false-recall levels indicate a higher degree of interconnections between the noncritical items and the critical one, and low false-recall levels indicate a lower degree.…”
Section: Drm Item Listsmentioning
confidence: 54%
“…Eleven 9-word lists were taken from Stadler and colleagues (Stadler et al 1999) when lists conformed to the specifications made by McEvoy and colleagues (McEvoy et al 1999) deemed necessary for stem completion tests. In order to investigate false memories under implicit stem completion instructions, critical items had to adhere to the specifications outlined by Graf and Schacter, (Graf and Schacter 1985), which had been followed by other researchers using the DRM paradigm (McKone and Murphy 2000).…”
Section: Encodingmentioning
confidence: 99%
“…However, subsequent research suggested that BAS (the associative strength from the studied items to the critical words) is the best predictor of false memories (e.g., Deese, 1959;Howe, Wimmer, & Blease, 2009;McEvoy et al, 1999;Robinson & Roediger, 1997;Roediger, Balota, & Watson, 2001). Consequently, in a recent DRM false-memory normative study conducted by Beato and Díez (2011), lists were constructed using BAS values, in line with other researchers who have pointed out the importance of employing BAS lists (e.g., Carneiro, Ramos, Costa, Garcia-Marques, & Albuquerque, 2011).…”
mentioning
confidence: 99%
“…With this procedure, researchers establish a cue-target relationship and calculate the proportion of participants who elicit a determined target in response to a particular cue. This proportion is considered to be an index of the associative strength between the two words (McEvoy, Nelson, & Komatsu, 1999). In the DRM paradigm, two types of lists are generally constructed with free association norms.…”
mentioning
confidence: 99%